LINGKUNGAN EKSTERNAL,,FAKTOR INTERNAL,DAN ORIENTASI PASAR PENGARUHNYA TERHADAP KINERJA PEMASARAN - Praetya, Dicky Imam (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2002)
The positive  effect of market orientation  on business performance had been well documented.  However, the identification  processes  of which factors  driving  the  degree  of market  orientation  and its relation with performance  have  been  the subject  of long  debate.  Some  scholars proposed that environmental conditions  moderate  market  orientation-performance  link,  while  the others found  empirical  evidence that  environmental factors  can  be treated as antecedents  of market  orientation.   Thereby  the present study is intended to develop an integrative model of market orientation in the context of business units of Bank  Bali.   The  model  describe  that  external  environment  and internal factors  are  hypothesised  as antecedents   of market  orientation.   The  model  subsequently  delineate  market  orientation  - marketing performance  link.  Bank Bali is chosen  due to recent conditions  can offer  an ideal venue for testing the models.  In this study,  the external environment is conceptualized along the dimensions of dynamism and munificence,  while internal factors  are comprised  of the dimensions offormalization and centralization. Furthermore,   market   orientation   consists   of  three   behavioural   components:   customer  orientation, competitor  orientation,   and interfunctional  coordination,  where  marketing  performance  incorporates efficiency,  effectiveness,  and adaptability  criteria into the measurement. The  sampling frame  of this  research  consist  of senior  managers  of 155  business  units of Bank  Bali whom  are randomly  selected.  Structural  Equation  Modeling  (SEM)  which  is run by Amos software  is employed to  analyze  the  data.   The result shows  that  environmental  dynamism positively   affects  the degree of market orientation while each of environmental  munificence, formalization,  and centralization has negative  impact.  Furthermore,  market orientation  is proven  to have a positive  effect  on marketing performance.  The empirical findings suggest  that senior managers of  business unit of Bank Bali should strive   to  improve   the  market  orientation   of  their   business  units  in  their  efforts   to  attain   higher performance  by analyzing  the  external  context  in  which  the business  unit  operates  and  the  internal context beforehand.  The theoretical implications and suggestions for future research  are also discussed.